the nth term of a sequence is given by this formula:
nth term = 62 - 5n
Find an expressipn, in terms of n, for the sum of the nth term and (n+1)th term of the sequence. thanks
Hello, abey_27!
It seems simple enough . . . Exactly where is your difficulty?
The $\displaystyle n^{th}$ term of a sequence is given by: .$\displaystyle a_n \:=\:62-5n$
Find an expression, in terms of $\displaystyle n$,
for the sum of the $\displaystyle n^{th}$ term and $\displaystyle (n+1)^{th}$ term of the sequence.
We have:. $\displaystyle \begin{array}{ccc}a_n &=& 62 - 5n \\
a_{n+1} &=& 62-5(n\!+\!1) \end{array}$
Therefore: .$\displaystyle a_n + a_{n+1} \;=\;[62-5n] + [62-5(n+1)] \;=\;119 - 10n$